(untitled) (Stato, Chiese e pluralismo confessionale, 2016)
Contributo sottoposto a valutazione. SOMMARIO: 1. Introduzione - 2. Libertà di religione ed espressione dell’identità culturale - 3. La costruzione delle moschee - 4. La vestizione del velo - 5. La pratica sommersa delle mutilazioni genitali femminili - 6. Il diritto di famiglia - 7. Il matrimonio - 8. I matrimoni poligamici - 9. I matrimoni forzati - 10. I diritti successori - 11. Ripudio e divorzio - 12. Kafalah e adozione - 13. Conclusioni. La necessaria unitarietà dell’ordinamento giuridico contro la discriminazione. Il caso delle giurisdizioni speciali shariaitiche: un’esperienza da non imitare. The Cultural Impact of Islamic Mass Immigration on the Italian Legal System ABSTRACT: Although Italy has been a country with a strong tradition of emigration, only in the last twenty-five years Italians have had to face the social, juridical and cultural problems related to high immigration hosted by this country. The majority of immigrants come from areas with Islamic religious tradition such as Northern and Central Africa and the Middle East. The cultural impact between the Italian Catholic tradition and the newcomers’ faith and customs has been very strong, often problematic. The aim of this paper is to investigate the most relevant issues between the cultural and legal aspects of Islamic culture pertaining to immigrants living in Italy with the Italian legal system. The legal areas proposed for the investigation are related to self-determination, personal integrity and family law, especially for analyzing the impact of cultural differences on public policies and social behavior. The methodology used regards a comparative and a multidisciplinary approach.